Macronutrient Deficiencies in Citrus: Nitrogen, Phosphorus, and Potassium - Mongi Zekri; Thomas A. Obreza (EDIS)
This document is SL 201, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First printed: January 2003.